The Potential of the Spatholobus littoralis Hassk Plant as an Antioxidant and Prediction of the Mechanism of Activity Against ROS1 Kinase Receptor in Silico - Atun, Sri; Aznam, Nurfina; Rasningtyaswati; Cahyani, Putri Verdiana Dwi; Izah, Lusiana Qotimatul; Danarjati, Wiwid Deswantari; Sangal, Adity Sangal (Malaysian Journal of Science, 2025)
Various phenolic compounds that exhibit antioxidant, anticancer, and anti-inflammatory activities are found in Spatholobus. Therefore, this study aimed to determine the antioxidant potential of Spatholobus littoralis wood in vitro and predict the mechanism of its activity against the ROS1 kinase receptor in silico. The ground-dried wood of S. littoralis was extracted with ethanol via maceration. The analysis of the total phenolic content (TPC) of extracts and fractions obtained from S. littoralis wood was determined by the Folin-Ciocalteu reagent. Similarly, the antioxidant activity was determined by the DPPH (2,2-diphenyl-1-picrylhydrazyl) and FRAP (The ferric reducing antioxidant power) method. The human ROS1 kinase enzyme (4UXL and 3ZBF) was used to determine the molecular mechanism of the interaction from the genus Spatholobus in silico. The total ethanol extract, chloroform, and ethyl acetate fraction of S. littoralis showed a high content of phenolic compounds and antioxidant activity. Phenolic compounds in plants of the genus Spatholubus also showed good activity against ROS1 kinase receptors (3ZBF and 4UXL). In conclusion, the S. littoralis plant has the potential to be developed for the discovery of new drugs.